FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP PASIEN GAGAL JANTUNG KRONIK DIRSUD KARAWANG - Grace Evelyn; Rina Feradwiyanti; Rismayanti Rismayanti (Sekolah Tinggi Pariwisata Mataram, 2021)
Chronic heart failure (CHF) is a complex syndrome that results in a poor quality of life. The prevalence of CHF increase up to 10% in the elderly. Different races have affect in different quality of life of the patient with CHF. The purpose of this study was to describe quality of life and to determine factors affecting quality patients CHF life RSUD Karawang. The research was non-experimental study (analytical descriptive) with a cross-sectional survey. This study was conducted on January – April 2015 with consecutive sampling method in cardiovascular polyclinic of RSUD Karawang. Quality of life were assessed with Minnesotta Living with Heart Failure Questionnaire (MLHF) and adherence were assessed with Morisky Medication Adherence Scale Questionnaire (MMAS-8). The risk factor that affect quality of life was age, sex, ejection fraction (EF), NYHA class, adherence, comorbid, Body Mass Index (BMI), duration of CHF, and class therapy were analyzed using Chi square test/Fisher exact test and Independent T-test. A total of 97 patients participated in the study. The result showed that the mean of score on physical dimension of MLHF is 16.72±8.68 and the mean of score on emotional dimension was 5.36 ±3.26. Women with CHF had better emotional rate than men (p<0,05). Based on the analysis, only ejection fraction have a significant difference with quality of life (p<0.05). Patient with EF <40% had worse quality of life than CHF patient with EF ≥40%. Hypertension and diabetic as comorbid and also the digoxin or angiotensin receptor blocker drug used affecting the physical condition of patients. (p<0.05).